2019
DOI: 10.1142/s0219887819501718
|View full text |Cite
|
Sign up to set email alerts
|

Study of thermal stability for different dark energy models

Abstract: In the present work, we have made an attempt to investigate the dark energy possibility from the thermodynamical point of view. For this purpose, we have studied thermodynamic stability of three popular dark energy models in the framework of an expanding, homogeneous, isotropic and spatially flat FRW Universe filled with dark energy and cold dark matter. The models considered in this work are Chevallier-Polarski-Linder (CPL) model, Generalized Chaplygin Gas (GCG) model and Modified Chaplygin Gas (MCG) model. B… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Subsequently, Chakraborty and collaborators [35][36][37][38] in a series of works have shown the stability criteria for different type of dark fluids and have presented the stability conditions (in tabular form) for different ranges of the equa-tion of state parameter. The present work is an extension of the interacting dark fluid model.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Chakraborty and collaborators [35][36][37][38] in a series of works have shown the stability criteria for different type of dark fluids and have presented the stability conditions (in tabular form) for different ranges of the equa-tion of state parameter. The present work is an extension of the interacting dark fluid model.…”
Section: Introductionmentioning
confidence: 99%
“…Further aspects are still to be considered: first, one could investigate how the present study interfaces with the results of [81], where it has been shown that some DE models, such as Chevallier-Polarski-Linder model, Generalized Chaplygin Gas and Modified Chaplygin Gas are thermodynamically stable for certain values of the model parameters. A potential path to explore is to see whether thermal stability for BHDE is achieved by considering different IR cutoffs and/or generalized interactions between the dark sectors of the cosmos.…”
Section: Discussionmentioning
confidence: 99%